Permeability and seismic velocity and their anisotropy across the Alpine Fault, New Zealand: An insight from laboratory measurements on core from the Deep Fault Drilling Project phase 1 (DFDP‐1). Issue 8 (19th August 2017) - Allen, M. J.; Tatham, D.; Faulkner, D. R.; Mariani, E.; Boulton, C.
Abstract: The Alpine Fault, a transpressional plate boundary between the Australian and Pacific plates, is known to rupture quasiperiodically with large magnitude earthquakes ( M w 8). The hydraulic and elastic properties of fault zones are thought to vary over the seismic cycle, influencing the nature and style of earthquake rupture and associated processes. We present a suite of laboratory permeability and P ( V p ) and S ( V s ) wave velocity measurements performed on fault lithologies recovered during the first phase of the Deep Fault Drilling Project (DFDP‐1), which sampled principal slip zone (PSZ) gouges, cataclasites, and fractured ultramylonites, with all recovered lithologies overprinted by abundant secondary mineralization, recording enhanced fluid‐rock interaction. Core material was tested in three orthogonal directions, orientated relative to the down‐core axis and, when present, foliation. Measurements were conducted with pore pressure (H2 O) held at 5 MPa over an effective pressure ( P eff ) range of 5–105 MPa. Permeabilities and seismic velocities decrease with proximity to the PSZ with permeabilities ranging from 10 −17 to 10 −21 m 2 and V p and V s ranging from 4400 to 5900 m/s in the ultramylonites/cataclasites and 3900 to 4200 m/s at the PSZ. In comparison with intact country rock protoliths, the highly variable cataclastic structures and secondary phyllosilicates and carbonates have resulted in an overall reduction in permeability and seismic wave velocity, as well as a reduction in anisotropy within the fault core. These results concur with other similar studies on other mature, tectonic faults in their interseismic period. Key Points: Low permeability and seismic velocity is associated with the damage zone of the Alpine Fault Zone, New Zealand The development of pervasive gouge‐filled and calcite‐filled fractures explains the low permeability and seismic velocity Seismic velocity anisotropy is low (<30%) due to the lack of preferred orientation of the fracture network in the fault damage zone